Centro de investigación del medio ambiente natural urbanizado del río Rímac - Revolledo Vicerrel, Edgar Junior (2021)
The Rímac River Urbanized Natural Environment Research Center is located in the Monserrate neighborhood in the Cercado de Lima district, Lima - Peru. The site is currently a large underutilized piece of land in the extreme north-west of the neighborhood and in front of the Rímac River, which serves as a deposit, storage and lowdensity housing. Surrounding the land, the urban space is not presented as an attractive and accessible space, but rather as a great wall that divides and prevents the neighborhood’s relationship with other urban fronts and, above all, that the relationship between the river and the city I do not know about. The project seeks to establish an urban and architectural relationship between the Monserrate neighborhood, its other urban fronts and the natural environment of the river. And in turn, a historical relationship with the events that took place in that space. In this way to be able to strengthen the cultural identity of the place, the social relations of the neighborhood, and the permanent connection of the river and the city.